Cost–effectiveness of ticagrelor in acute coronary syndromes. (February 2013) - Henriksson, Martin; Janzon, Magnus
Ticagrelor is a reversibly binding oral P2Y12 inhibitor, which belongs to a novel chemical class of antiplatelet agents named cyclopentyl-triazolo-pyrimidines. Ticagrelor administered with acetylsalicylic acid has been shown to reduce the rate of the composite end point of death from vascular causes, myocardial infarction or stroke without an increase in the rate of overall major bleeding compared with clopidogrel plus acetylsalicylic acid in patients with acute coronary syndromes. In addition to these clinical findings, it has been shown that the cost per quality-adjusted life year with ticagrelor is below the generally acceptable thresholds for cost–effectiveness compared with clopidogrel. Healthcare decision-makers need to consider the costs and cost–effectiveness when prioritizing treatments among scarce healthcare resources. This is of particular importance in cases similar to ticagrelor, where the novel treatment is expected to improve effectiveness at a higher acquisition cost. In this article, the authors review and discuss the health–economic evidence of ticagrelor.